2000
DOI: 10.1055/s-2000-8330
|View full text |Cite
|
Sign up to set email alerts
|

Anomalies and Variants of the Endoscopic Anatomy for Third Ventriculostomy

Abstract: Anatomic anomalies are a frequent finding during ETV. Successful perforation and control of the hydrocephalus correlates with the absence of anatomic anomalies. Most anatomic variants have the potential to increase the operative risk. With the exception of the thickened third ventricular floor, MR imaging allows us to identify all anatomic anomalies preoperatively, and enables the neurosurgeon to weigh the operative risk in a patient with an anatomic anomaly against the chance to perform ETV successfully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 20 publications
1
30
1
3
Order By: Relevance
“…This was similar to certain studies by other authors [1,16,17]. Dysmorphic brains already present prior to ventriculostomy were not found to be a predictor for poor outcome in our series compared to other studies [3,19]. Size of the third ventricular floor and ventricle ratio was also not found to be a predictor of outcome as suggested by various studies [4,7,13,18].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This was similar to certain studies by other authors [1,16,17]. Dysmorphic brains already present prior to ventriculostomy were not found to be a predictor for poor outcome in our series compared to other studies [3,19]. Size of the third ventricular floor and ventricle ratio was also not found to be a predictor of outcome as suggested by various studies [4,7,13,18].…”
Section: Discussionsupporting
confidence: 77%
“…Numerous studies [1,5,[15][16][17][18]20] support this. Overall, our findings differ from one paper [20] which dealt with normal pressure hydrocephalus and other publications on abnormal anatomy and third ventricular floor width [3,4].…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…2). We believe that a perpendicular trajectory is almost essential for successful perforation of the tentorium: a smaller angle would result in slipping of the perforation instruments as we have observed in tense and steeply declining third ventricular floors during ETV [28]. Only in neonates is the tentorium thin and fragile enough to allow perforation with bipolar coagulation; endoscopic transtentorial ventriculocystostomy in older children is not considered to be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the issue of ETV in young children remains a matter of discussion. We have shown that the success rate of ETV is related to anatomic anomalies and variants [28], with poorer rates in thickened and steeply declining third ventricular floors. (3) Stent placement from the third ventricle through the aqueduct into the posterior fossa cyst is a risky procedure, because of the delicate periaqueductal structures.…”
Section: Discussionmentioning
confidence: 99%